El acceso a recursos genéticos en pueblos indígenas y el Convenio de Diversidad Biológica. (2013)
After the Convention on Biological Diversity a deepening debate is taking place concerning the protection of genetic resources and traditional knowledge of indigenous peoples; which involves a discussion about the application of biotechnology and its impact on the protection of life and environment; and an analysis of the participation of these in the process of developing strategies to protect their resources and traditional knowledge; which gives rise to legal pluralism from the development of the different Conferences of the Parties; which today allows for a more comprehensive regulatory framework and a possibility of its strengthening